Исследование возможности получения наноструктур на твердом сплаве ВК8 при действии импульсного лазерного излучения малой длительности - Костюк, Геннадий Игоревич; Размаджуи, Бехзад (НТУ "ХПИ", 2016)
Исследованы максимальные температуры и максимальные температурные напряжения при действии лазерного излучения плотностью теплового потока 10¹²...10¹⁶ Вт/м² и времени действия 10⁻¹⁶...10⁻¹⁰ с. Также для этих режимов исследованы скорости нарастания температуры и получены пространственные картины зависимостей объёма нанокластера от плотности теплового потока и времени его действия при двух размерах пятна 5·10⁷ и 10⁻⁶ м. Всё это позволяет найти технологические режимы получения наноструктур в твёрдом сплаве ВК8 и выбирать их с учётом возможности технологических установок и минимального энергопотребления.

In the paper, the maximum temperature and maximum thermal stresses under the action of laser radiation heat flux from 10¹²...10¹⁶ W/m², and the time of action of 10⁻¹⁶...10⁻¹⁰ seconds. Also for these regimes investigated the rate of rise of temperature and obtained the spatial pattern dependencies nanocluster volume of the heat flux density and the time of its action in two sizes 5∙10⁷ and 10⁻⁶ m. All this allows you to find process conditions for fabricating nanostructures in solid alloy WC0,92+Co0,08 and select them taking into account the possibility of technological installations and minimal power consumption.
Study opportunities nanostructures on hard alloy WCCo8 under pulsed laser radiation of short duration
Keywords: наноструктуры; твердый сплав; фемтосекундный лазер; nanostructures; hard alloy; femtosecond laser